HUBUNGAN ANTARA STRES AKADEMIK DENGAN KUALITAS TIDUR PADA MAHASISWA YANG MENYUSUN SKRIPSI - Dewi Cahyani Emi Mulyati; Ahmad Ridfah; Nur Akmal (Jurnal Online Keperawatan Indonesia, 2023)
Final year students are individuals who are preparing a thesis to complete higher education at a university. This research aims to determine the relationship between academic stress and sleep quality in students writing their thesis at Makassar State University. This research uses quantitative methods. The number of samples used in this research were 300 students who composed their thesis taken by sampling technique, namely Aksidental Sampling. Data collection used a questionnaire and data analysis used the Spearman Rank statistical test. According to the results of univariate analysis of the academic stress variable, it is discovered that most of the respondents experienced moderate academic stress. Meanwhile, the results of univariate analysis of sleep quality variables revealed that most of the respondents had quality sleep when writing their thesis. Based on bivariate analysis with the Spearman Rank test, a correlation coefficient of 0.266 (p = 0.000) was gained so that there was a relationship between academic stress and sleep quality in students writing theses at Makassar State University.